PELATIHAN PEMANFAATAN VIDEO MARKETING MELALUI INSTAGRAM TV (IGTV) SEBAGAI PENGUATAN PRODUK/BRAND KOPI ARABIKA KALIANGKRIK MAGELANG - Widhi Nugroho (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
The use of Instagram by the Mekar Lestari Farmer Group started about 2 years ago. However, the content on Instagram with the kopi_arabika_magelang account only focuses on media documentation and publication of farmer group activities. Starting from this, it is necessary to use social media such as Instagram and Instagram TV (IGTV) with the aim of managing the promotion and marketing of coffee products with the Kaliangkrik Coffee brand. This is necessary to remember the power of social media as a means of promotion and marketing product are very effective. By actively involving members of the Mekar Lestari Farmer Group in making marketing video, the training is participatory method. The method used is the participation action research (PAR) approach. The strategy taken is to explore partner problems by identifying problems, especially in terms of training on making marketing video through Instagram TV (IGTV) in the form of video ads and Instagram Stories which aim to strengthen the Kaliangkrik Coffee product / brand. Keywords: coffee, kaliangkrik, instagram TV (IGTV), participation action research (PAR), video marketing.